Pengembangan Media Mobile Learning Berbasis Android Untuk Siswa SMA Kelas X Pada Materi Ikatan Kimia - Fence Artemas Ambalau; Ni Wayan Suriani; Septiani Ch Palilingan (Chemistry Department, Universitas Negeri Manado, 2022)
This study aims to: (1) Produce android applications as a support source for learning chemistry in class X. (2) Determine the feasibility of android applications. The research and development design uses the Borg & Gall development design (R&D) model, there are 10 steps that must be taken in development research. The ten steps were simplified by Ghozi into four steps, namely: (1) preliminary research, (2) design stage, (3) development stage and (4) testing phase. Data collection techniques were carried out by observation, interviews and questionnaires. The testing phase is carried out by validating the product by media experts and material experts, testing on the first user (teacher) and testing on the end user (student). The data analysis technique used is descriptive analysis technique. The results of this study are: (1) an android application model for appropriate learning media on chemical bonding material which includes: preparation, material mapping, development, and validation; (2) the feasibility of an android application for appropriate learning media on chemical bonding material. Based on the converted average assessment with a percentage range of 0% -100%, it is obtained that the value of media experts is assessed from 32 points of assessment indicators, a score of 103 and a percentage of 78.33% is included in the